(untitled) (Physical Education, Health and Social Sciences, 2026)
This study provides an in-depth study of the spatial distribution and concentration of retail businesses in Faisalabad and Lahore Cities. In this study used grid cluster locations and graduated colour systems to analyse the spatial distribution of shops across several categories. The findings show systematic spatial patterns in the distribution of retail businesses, indicating the existence of relevant forces that go beyond random behaviour. The outcome of the study emphasizes the significant influence of geographic distribution on the economic structure of both cities. The use of grid cluster location maps, in conjunction with graduated colour schemes, provides an excellent representation of the spatial distribution of shops across different categories. By conducting a comprehensive examination, this study offers valuable insights into the densities and concentrations of clusters, thereby empowering stakeholders with the ability to make well-informed decisions. Statistical methodologies such as Moran’s Index, z-scores and p-values serve to highlight the importance of spatial autocorrelation, a phenomenon that exerts significant effects on commercial strategies, public policies, and urban developmental plans. This study highlights the necessity for further investigation into the factors that contribute to the Distribution patterns. The present study analyses the Cost of running a business and the influence of varying shop sizes on retail shops, ranging from 125 to more than 300 square feet. This study thoroughly investigates the impact of different shop sizes on both customer experiences and financial aspects, including factors such as rent, utilities, taxes, and salaries. Pie charts to represent the expenditures across various shop sizes, offering detailed insights into several categories of retail stores. This study provides a comprehensive analysis of the study’s findings, resulting in practical proposals. The suggested ideas are designed to address the needs and interests of many stakeholders, such as urban planners, entrepreneurs, and policymakers. In conclusion, this study provides useful insights into the geographical distribution of Retail shops in Faisalabad and Lahore. The observed non-random grouping patterns emphasize the essential role of deliberate choices in urban planning, economic growth, and business strategies. The guidance provided offers valuable insights for both individuals and organisations, advising them in making well-informed decisions and enhancing the economic conditions of both urban centers.